Process Developments And Applications Around The Powder In Tube Technique - Auguste, J.-L.; Humbert, G.; Leparmentier, S.; Blondy, J.-M.; Martin, P.-O.; Delaizir, G.; Litzkendorf, D.; Grimm, S.; Schuster, K. (ALT Proceedings, 2026)
The purpose of this presentation is to give an overview of techniques available to produce original optical fibers and application dedicated. Some alternative fabrication solutions to the well-know stack and draw technique will be developed, following by the interest to join the stack and draw technique to other ones like Repusil® Technique, Rod in Tube and finally the Powder in Tube methods, first described by the Bell Lab in the seventies and up to date since some years by several groups in the world. Realization of performing optical devices such as light sources or optical sensors can be purposed by this two last original ways.